Analysis of Leadership Style and Employee Work Discipline in Improving Organizational Performance - Rusdin Ndua; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Al-Qalam Institue, 2025)
This study examines the relationship between the Village Head's leadership style and employee work discipline at the Padang Tumbuo Village Office, Ampana Kota District, Tojo Una-Una Regency. Quality human resources (HR) are crucial in achieving organizational goals, particularly in the public sector. This study employed a qualitative design with a case study approach, with data collected through in-depth interviews and direct observation. The results indicate that the Village Head's democratic-participatory leadership style, with directive and transformational touches, plays a significant role in improving employee work discipline. The Village Head provides appreciation, motivation, and direct involvement in work activities, creating a positive work atmosphere. However, challenges remain in discipline, such as tardiness and a lack of understanding of duties and responsibilities. This study suggests the importance of regular training, a more effective attendance system, and objective performance evaluation. The contribution of this study is to enrich the literature on the influence of leadership style on employee discipline in village government.